Pluripotent stem cells from the perspective of developmental potential and their characteristics - In-Won Lee; Sang-Ki Baek; Yeon-Ji Lee; Tae-Suk Kim; Bo-Gyeong Seo; Cheol Hwangbo; Joon-Hee Lee (Journal of Animal Reproduction and Biotechnology)
Pluripotent stem cells (PSCs) are undifferentiated cells with the potential to develop into all cell types in the body. They have the potential to replenish cells in tissues and organs, and have unique properties that make them a powerful tool for regenerative therapy. Embryonic stem cells (ESCs) derived from the inner cell mass of the blastocyst of pre-implantation embryo and epiblast stem cells (EpiSCs) derived from the epiblast layer of post-implantation embryo are the well-known PSCs. These stem cells can differentiate into any of three germ layers of germ cells (endoderm, mesoderm and ectoderm). Additionally, induced pluripotent stem cells (iPSCs) refer to adult somatic cells reprogrammed to return to the pluripotent state by introducing specific factors. This is a breakthrough in stem cell research because ethical concerns such as fertilized embryo destruction can be avoided. PSCs have tremendous potential in treating degenerative cells by generating the cells needed to replace damaged cells, which can also allow to generate specific cell types to study the mechanisms of the disease and create disease models that screen for potential drugs. However, if the proliferative capacity of PSCs is not controlled, there is a risk that tumors will form, as this can lead to uncontrolled growth in their proliferative capacity. In addition, when PSCs are used for therapeutic purposes, there is a risk that the body’s immune system rejects the transplanted cells when the transplanted cells do not originate from the patient’s own tissue. Taken together, PSC is the foundation of stem cell research and regenerative medicine, providing disease treatment and animal development understanding. We would like to explain the classification of PSCs based on their developmental potential, the types of PSCs (ESCs, EpiSCs and iPSCs), their pluripotent status (naïve vs. primed) and alkaline phosphatase (AP) in PSCs and PSCs in domestic animals.